2008
DOI: 10.1111/j.1582-4934.2008.00277.x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed development of interstitial cells of Cajal in the ileum of a human case of gastroschisis

Abstract: The Interstitial Cells of Cajal (ICC) are responsible for rhythmic electrical activity. A paralytic ileus is present in gastroschisis (GS), a malformation due to a defective closure of the abdominal wall through which part of the intestine herniates during pregnancy. In experimental GS, ICC morphological immaturity was shown in the rat foetus at-term but it could not be demonstrated whether differentiation is accomplished post-natally. For this purpose we morphologically investigated ICC, as well as enteric ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 30 publications
1
13
0
1
Order By: Relevance
“…5,6 Loss of ICC function can lead to symptoms that might traditionally have been considered defects in myogenic or neurogenic control mechanisms. However, KIT labeling showed that the structural integrity of ICC is aberrant in a variety of GI dysmotilities, including achalasia, 7,8 diabetic gastroenteropathy, 911 hypertrophic pyloric stenosis, 12 gastroschisis, 13 intestinal pseudoobstruction, 1417 slow transit constipation, 1820 Hirschsprung’s disease, 21,22 Crohn’s disease, 23,24 and inflammatory bowel disease. 2527 …”
mentioning
confidence: 99%
“…5,6 Loss of ICC function can lead to symptoms that might traditionally have been considered defects in myogenic or neurogenic control mechanisms. However, KIT labeling showed that the structural integrity of ICC is aberrant in a variety of GI dysmotilities, including achalasia, 7,8 diabetic gastroenteropathy, 911 hypertrophic pyloric stenosis, 12 gastroschisis, 13 intestinal pseudoobstruction, 1417 slow transit constipation, 1820 Hirschsprung’s disease, 21,22 Crohn’s disease, 23,24 and inflammatory bowel disease. 2527 …”
mentioning
confidence: 99%
“…Further support for this cause of delayed intestinal motility comes from a clinical case that showed delayed maturation of the ICC network and enteric neurons at birth in a specimen of normal-looking small bowel from a human neonate with gastroschisis who required resection because of bowel ischemia. 22 Interestingly, examination of a second specimen taken 1 month later during surgery to restore continuity showed improved maturation of the ICC network and enteric neurons. 22 Similarly, decreased expression of c-kit has been consistently observed in the proximal segment of small bowel with intestinal atresia in a large series of 23 patients 15 Impairment of ICC morphology and network in our experimental gastroschisis study may thus be secondary to functional obstruction.…”
Section: Discussionmentioning
confidence: 97%
“…22 Interestingly, examination of a second specimen taken 1 month later during surgery to restore continuity showed improved maturation of the ICC network and enteric neurons. 22 Similarly, decreased expression of c-kit has been consistently observed in the proximal segment of small bowel with intestinal atresia in a large series of 23 patients 15 Impairment of ICC morphology and network in our experimental gastroschisis study may thus be secondary to functional obstruction.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to serving as a chemotactic factor for eosinophils, eotaxin may be involved in recruiting T cells that express the eotaxin receptor CCR3 to the intestine (50) and may adversely affect bowel motility (51). Locally, T cell infiltration and inflammatory cytokine production in the intestines may contribute to bowel dysmotility by multiple mechanisms, including damaging the interstitial cells of Cajal (52), which have been shown to be developmentally delayed in gastroschisis (53). …”
Section: Discussionmentioning
confidence: 99%